Penentuan Jenis dan Wilayah Prioritas Pelayanan Sistem Pengelolaan Air Limbah Domestik di Kecamatan Rancasari Kota Bandung - Eka Wardhani,; Hendra Hermawan, (Journal Serambi Engineering, 2023)
Rancasari Subdistrict is located in Bandung City, comprises four urban villages, encompassing 0,19 km2 with six blocks of light slum areas. Slum areas are areas that tend to have more vulnerable environmental conditions due to the minimal availability of environmental infrastructure, one of which is sanitation facilities. Based on this, Rancasari subdistrict needs to determine the type of domestic wastewater management system service and priority service areas. Determination of the service type of domestic wastewater management system is determined based on Attachment 1 of Regulation of the Minister of Public Works and Public Housing Number 4 of 2017, while priority areas are determined based on Bandung City Regional Regulation Number 5 of 2022, Regional Regulations Bandung City Number 10 of 2015, and the area of slum settlements in each village. Rancasari Subdistrict is suitable for on-site system, while the main priority area is Manjahlega Village, then Mekarjaya, Derwati, and Cipamokolan. It is necessary to develop domestic wastewater management system facilities in the main priority area in the form of development of existing communal septic tanks and communal wastewater treatment facility, as well as the closure of piped domestic wastewater disposal facility leading to the Cidurian River to stop open defecation.